Does Kasai operation prior to liver transplantation affect peri-operative outcomes in children with biliary atresia? - Choungboonsri, Chatdow; Sutthatarn, Pattamon; Nonthasoot, Bunthoon; Sirichindakul, Booncho; Taesombat, Wipusit; Sutherasan, Maythee; Nivatvongs, Supanit; Vejchapipat, Paisarn (Chulalongkorn Medical Journal, 2021)
Background: Biliary atresia is the most leading cause of death from liver disease in children and the most common indication for pediatric liver transplantation. Although portoenterostomy is the mainstay treatment of biliary atresia, there were some studies found that prior portoenterostomy would adversely affect the liver transplant. Objectives: To compare the peri-operative outcomes between biliary atresia (BA) children having Kasai operation and those with primary liver transplantation (LT). Methods: Children with BA (0 - 15 years) who underwent LT between 2003 and 2017 were reviewed. Patients were categorized into 2 groups (Group A: BA children undergoing Kasai operation prior to liver transplantation; and, Group B: BA children receiving primary LT, without Kasai operation). Variables that might affect the outcomes were compared. Unpaired t - tests, non-parametric tests, or Fisher’s exact tests were used. Data are expressed as mean and standard deviation. Results: Fifty-two patients were recruited: Group A (36 patients) and Group B (16 patients). Subjects in Group A had older age when having LT (68.5 77.5 vs. 12.2 3.3 months, P = 0.006) and lower pediatric end-stage liver disease (PELD) score (age <12 years, 13.1 8.8 vs. 20.5 6.7, P = 0.007). However, there was no statistically significant difference in operative time (605.5 129.6 vs. 563.4 74.9 min, P = 0.235), warm ischemic time (49.3 14.1 vs. 45.8 7.3 min, P = 0.369), intraoperative blood loss (149.5 248.8 vs. 117.56 126.93 mL/kg, P = 0.635), total ICU stays (9.9 9.0 vs. 6.9 5.9, P = 0.232) and hospital stays (45.3 31.4 vs. 48.2 38.3, P = 0.772). Postoperatively, there was no significant difference regarding vascular (3/36 vs. 2/16, P = 0.637) and biliary (5/36 vs. 2/16, P = 1.0) complications between both groups. Additionally, 3-year survival rates following LT between 2 groups were similar (87.8% vs. 93.7%, P = 0.583). Conclusions: Kasai operation probably delayed the need for LT. The severity (PELD score) was less at the time of LT in children with Kasai operation. It did not adversely affect the peri-operative outcomes of BA patients having liver transplantation. Peri-operative complications, early outcomes and survival rates were comparable.